La mobilisation des travailleurs surendettés en Espagne : la double peine économique - Quentin Ravelli (La Nouvelle Revue du Travail)
Since the 2008 crisis, debt has become a powerful engine for mobilization in many countries, from Greece to the United States, from South Africa to Iceland. In Spain, working-class debt has led to foreclosures, evictions, and mass contestation. At the core of this process lies a double economic burden: indebted construction workers are hurt by the crisis both as unemployed producers and as consumers who can no longer pay off their loans. Their debts are higher than their low incomes and the collapse of home prices generates a situation of negative equity, from which they can escape only through collective struggle. Women, often cleaners and often immigrants from Spanish former colonies, are essential protagonists of this struggle. Far from a spontaneous uprising, this mobilization relies on the ability to organize by collectivizing individual anger, via an emotional dramaturgy of debt.